2017
DOI: 10.5812/ijp.10015
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Neonatal Pain Management from the Perspectives of Nurses and Physicians in a Neonatal Intensive Care Unit: A Qualitative Study

Abstract: Background: Despite scientific advances on pain measurement and intervention, pain management for infants has remained a challenge for health teams. This is because infants are not able to talk and defend themselves when they are in pain. Prevention of pain is important, not only because it is an ethical expectation, but also because repeated painful exposures can have harmful consequences. The aim of this study was to explore factors influencing neonatal pain management from the perspectives of nurses and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(58 citation statements)
references
References 27 publications
2
55
0
Order By: Relevance
“…Similarly, a study conducted in Iran on pain management perceptions of the neonatal nurses in NICU and neonatal units revealed that the infant pain management policy was associated with practice of nurses in managing infant pain. 23 This implies that the presence of an infant pain management policy in the unit is a key point in the practice of neonatal pain management and results in effective managing of pain in neonates among nurses. As a result, the presence of an infant pain management policy and management issues was key to following good practice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Iran on pain management perceptions of the neonatal nurses in NICU and neonatal units revealed that the infant pain management policy was associated with practice of nurses in managing infant pain. 23 This implies that the presence of an infant pain management policy in the unit is a key point in the practice of neonatal pain management and results in effective managing of pain in neonates among nurses. As a result, the presence of an infant pain management policy and management issues was key to following good practice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other studies. [7,11,12,16,23] The findings of low knowledge on neonatal pain management were likely related to the lack of formal teaching in nursing school and lack of continuing professional education in the hospital. Furthermore, the neonatal units lacked a pain management protocol or pain assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…Several international studies, [11][12][13] reported that pain in neonates is often not recognised and undertreated. There are very few studies in Rwanda on patient pain management, and there were no published studies on neonatal pain in 2017 when this research was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…There is no gold standard for the neonatal pain measurement in current medical services [6,7], however the Joint Commission on Accreditation of Health Care (JCAHO) recommends choosing a valid measuring instrument, reliable and in accordance with age; and at present, more emphasis is on the description of physical function due to pain [8,9]. The multidimensional scale of pain assessment in neonates that is most studied are Neonatal Infant Pain scale (NIPS), Premature Infant Pain Profile (PIPP) and Neonatal Facial Coding System (NFCS) [10]. Among the three measuring instruments, PIPP is more detailed in measuring physiological aspects.…”
Section: Introductionmentioning
confidence: 99%